Lithuanian Police Šiauliai (14th) and Panevėžys (10th) Battalions (1941–1944) - Bubnys, Arūnas (Genocidas ir rezistencija, 2010)
On the basis of archival documents and historical literature, the article attempts to recreate the history of the two Lithuanian police battalions, in Šiauliai and Panevėžys, the most important stages in their activities and events, to reveal the similarities and differences, personnel, and suffered losses. The history of those battalions has not been studied specially either by Lithuanian or foreign historians. Basing on the analysis of the facts found, conclusions are being drawn up. The history of both battalions has more similarities rather than differences. Both of them were formed at the same time – in August 1941. Šiauliai and Panevėžys were the only cities in Lithuania, except for Kaunas and Vilnius, where the units of the battalion size were formed. Both battalions were founded on a voluntary basis. The participants of the June 1941 Uprising and the officers of the parapolice troops, riflemen, the former Lithuanian Army officers and non-commissioned officers mostly started their service here. The battalion fighters guarded the objects of military importance, railways and big industrial enterprises. In the summer and autumn 1941, both battalions together with other German and Lithuanian police units, participated in the Jewish massacre in the Šiauliai, Panevėžys and Telšiai counties. About 180 fighters from both battalions could participate directly in the massacre. The partisans of the Šiauliai and Panevėžys battalions would confront Soviet partisans very seldom; therefore sustained casualties were not heavy. Heavier losses constituted the fighters who were absent without leave. The Šiauliai and Panevėžys battalions operated during the entire period of their existence in Lithuania (except for smaller units of battalions, transferred to other Lithuanian police battalions) and were not sent for service outside the territory of Lithuania. The Šiauliai battalion operated until the end of the Nazi occupation and was dissolved at the end of the summer of 1944. The Panevėžys battalion was disbanded in January 1943, transferring the greater part of the fighters for service in the Šiauliai battalion.
Keywords: Lithuania; German occupation; collaborators; police battallions